Electrochemical behavior of praseodymium on the W and Al–Zn electrodes in LiCl–KCl eutectic: A comparison study. (5th December 2019) - Liu, Ya-lan; Ren, Hao; Yin, Tai-qi; Yang, Da-wei; Chai, Zhi-fang; Shi, Wei-qun
Abstract: A new active Al–Zn electrode for recovering praseodymium (Pr) from spent nuclear fuel in chloride molten salts was proposed in this work. The electrochemical behavior of Pr(III) ions dissolved in LiCl–KCl eutectic and its co-reduction with Al(III) and Zn(II) ions on the W electrode as well as its reduction at the liquid Al–Zn electrode were studied and compared. In addition, the diffusion coefficient of Pr(III) ions in melt was evaluated using semi-integral and semi-differential techniques, respectively. The results showed that the number of redox signals corresponding to Pr–Zn intermetallic compounds are more than that for Pr–Al intermetallics. Potentiostatic and galvanostatic electrolysis were both carried out on various electrodes to identify the formation of different Pr-containing alloys. The characterizations for cathodic deposits obtained were accomplished by using X-ray diffraction (XRD) and scanning electron microscopy with energy dispersive spectroscopy (SEM-EDS). The work described here can broaden the applications of Al–Zn alloys and highlight its potentials in future molten salt electrolysis based spent fuel pyroprocessing.